Identification of Functional Domains of Bordetella Dermonecrotizing Toxin - Kashimoto, Takashige (American Society for Microbiology, 1999)
Bordetella dermonecrotizing toxin (DNT) stimulates the assembly of actin stress fibers and focal adhesions by deamidating Gln63 of the small GTPase Rho. To clarify the functional and structural organization of DNT, we cloned and sequenced the DNT gene and examined the functions of various DNT mutants. Our analyses of the nucleotide and amino acid sequences revealed that the start codon of the DNT gene is a GTG triplet located 39 bp upstream of the reported putative initiation ATG codon; consequently, DNT contains an additional 13 amino acids at its N-terminal end. All of the N-terminally truncated mutants were found to modify Rho. The shortest fragment of DNT possessing the Rho modification activity consists of amino acids from Ile1176 to the C-terminal end. This fragment overlaps the region homologous to Escherichia coli cytotoxic necrotizing factors (CNFs), which show activity similar to that of DNT. The introduction of a mutation at Cys1305 located in the highly conserved region between CNFs and DNT eliminated the activity, indicating that this domain is the catalytic center of DNT. The N-terminal fragment (1 to 531) of DNT failed to modify Rho but reduced the DNT-induced polynucleation in MC3T3-E1 cells when simultaneously added with the holotoxin, suggesting competitive inhibition in the receptor-binding or internalizing step. Our finding that DNT consists of an N-terminal receptor-binding and/or internalizing domain and a C-terminal catalytically active domain may facilitate analysis of the overall action of the toxin on the mammalian target cells.